(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
A comprehensive study of specific semantic fields is one of the studies in this direction. Indeed, the analysis of specific semantic fields of words has its own philosophical value. Because the people will rebuild and shape their worldview on the basis of their history, traditions and life experience. Just as the analysis of microsystems allows us to reveal the semantic structure of words, it also allows us to show the general lexical system of a language. One of the most important tasks of modern semantics is to identify microsystems within the verb, to study their synonymous, antonymic and other semantic relations of internal structural elements, thus determining the place of each semema in the lexical system